Physicomechanical properties of bioplastics from kappa-carrageenan and cassava peel starch : Sifat fisikomekanik bioplastik dari campuran kappa-karagenan dan pati limbah kulit singkong - Fadhallah, Esa Ghanim; Fahlevi, Frily Aurelia Salshabila; Ashari, Hersan Pratama; Anggriani, Yosnita; Dewi, Ni Made Puspa; Meranda, Dea; Mulianingsih, Elita; Haidawati, Haidawati; Febriati, Nurullia (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Kappa-carrageenan, derived from red seaweed, is well-known for its excellent film-forming properties and is widely used as a bioplastic material. It is possible to improve the physical and mechanical properties of bioplas-tics by mixing kappa-carrageenan with cassava peel starch and polyvinyl alcohol (PVA) as a reinforcement. The goal of this study is to find the best combination of kappa-carrageenan and cassava peel starch for bio-plastic based on its thickness, tensile strength, elongation, and water vapor transmission rate (WVTR), as specified in JIS Z 1707. A completely randomized block design (CRBD) was employed with varying ratios of kappa-carrageenan and cassava peel waste starch. The findings show that the mixtures of kappa-carrageenan and cassava peel starch had a big effect on all of the bioplastic’s physical and mechanical properties, except for its density. All bioplastic formulations met the JIS standard for tensile strength and elongation. Higher starch con-centrations significantly improved the barrier properties by reducing WVTR and water absorption. However, increasing starch concentration enhanced elongation while decreasing thickness, tensile strength, and Young’s modulus, resulting in slower biodegradation. The best mix, which had 4% starch and 1% kappa-carrageenan, was thickest at 0.35 mm, a tensile strength of 1.14 MPa, an elongation of 25.78%, and a WVTR of 18.47 g/m²/day (Grade 3). The results show that kappa-carrageenan and waste starch from cassava peel can be used to make bioplastics that meet the standards for physical and mechanical properties. This could also help reduce plastic pollution in the future.